A new treehopper species of Cladonota (Stål) (Hemiptera: Membracidae:Membracinae: Hypsoprorini) from Mexico - Flynn, Dawn J.; Gálvez, Juan Enrique Benítez (Zootaxa, 2021)
A new species of treehopper from Puebla, Mexico is described, Cladonota (Lecythifera) crucifixa n. sp., with illustrations and biological notes and compared with C. hoffmanni (Peláez, 1940).